Blockchain, FinTechs and their relevance for international financial institutions - Emmanouil Davradakis; Ricardo Santos (European Investment Bank (EIB), 2019)
The purpose of this working paper is to provide a primer on financial technology and on Blockchain, while shading light on the impact they may have on the financial industry. FinTechs, the financial technology and innovation that competes with traditional financial methods in the delivery of financial services, has the potential to improve the reach of financial services to the broader public and facilitate the creation of a credit record, especially in the developing world. Some Blockchain applications like cryptocurrencies, could be problematic as cryptocurrencies cannot substitute traditional money due to the high risk of debasement, luck of trust and high inefficiencies relating to the high cost in electricity and human effort required to clear cryptocurrency transactions. Cryptocurrencies' high volatility renders it a poor means of payment and store of value, while resembling a fraudulent investment operation. Yet, other Blockchain applications, like Blockchain securities, could facilitate the functioning of an International Financial Institutions (IFI) due to the volume of securities they issue as Blockchain securities enable an almost instantaneous trade confirmation, affirmation, allocation and settlement and reconciliations are superfluous releasing collateral to be used for other purposes in the market. IFIs could promote awareness and understanding about Blockchain technology among different IFI services and launch Blockchain labs in order to pilot projects that can improve governance and social outcomes in the developing world. Financial inclusion, at the core of IFI's mandate, could be enhanced by investing into FinTechs who facilitate access to payment systems. IFIs could also ponder the development of Blockchain software aimed at improving transparency and efficiency in public resources that finance development projects. IFIs could promote Blockchain applications in several sectors like agricultural lending where Blockchain technology is used in the supply chain in order to improve transparency and efficiency in agricultural and commodity production. Other sectors include transport and logistics and even energy distribution. IFIs could benefit by utilizing FinTechs' knowhow in the analysis of big data in order to understand better the investment gaps and the financing needs of prospective clients. Finally, FinTechs' knowhow could be used by IFIs in order to streamline their internal processes concerning credit underwriting and risk management.
Keywords: 330